HEALTH PROMOTION OF THE ELDERLY IN BAN KRUAT DISTRICT BURIRAM PROVINCE - Intarangkul, Thittayawadee (PEOPLE: International Journal of Social Sciences, 2017)
There is concern that the ageing of the population in Thailand will put unsustainable pressure on public spending, with particular concerns about rising health costs and the ability of the health system to serve the increasing numbers of older people needing care. Undoubtedly, ageing will present challenges to the health-care system given the larger number of older people, the fact that many health conditions and, associated disability become more common with age, and that older people are higher users of health services. This study analyses the key areas of challenge for the health system as it adapts to an ageing population. It then sets out ways Thailand’s health system needs to adjust to meet the issue of an ageing population. Specifically, the purpose of the study was to study health promotion for the elderly in Ban Kruat District Buriram Province, Thailand. The study area is in Ban Lahansai, Tambon Hin Lad, Amphur Ban Kruad, Buriram Province. The methodology used in this study is qualitative research. The sample group is specifically selected,consists of five elderly people aged more than 6 years old and 5 community leaders that reside in Ban Lahan Sai, Tambon Hin Lad, Amphur Ban Kruad, Buriram Province. The study uses Qualitative Methodology of Ethnographic, In-depth interview technique, note taking from focus group discussion and content analysis. This case study found that the current policies and practices of health promotion for the elderly in Thailand is not suitable for the elderly age group.